Evaluation of promising strawberry (Fragaria x ananassa Duch.) varieties for Wayanad - Muhammed aslam (Department of Fruit Science, College of Horticulture, 2017)
The experiment entitled “Evaluation of promising strawberry (Frageria x ananassa Duch.) varieties for Wayanad” was undertaken at Regional Agricultural Research Station, Ambalavayal, Wayanad, Kerala during the year 2016-17. Performance of five strawberry varieties viz., Crystal, Winter Dawn, Sweet Charlie, Sabrina and Eliyana were evaluated under open and polyhouse conditions. Maximum plant height (32.31 cm), number of leaves (26.20) and plant spread (31.41 cm) were recorded in variety Winter Dawn followed by Sweet Charlie under both growing systems. Number of flowers (16.24) and number of clusters per plant (10.13) was significantly higher in variety Winter Dawn followed by Sweet Charlie. Minimum days to first flowering were observed in the variety Crystal (45.21). Maximum number of fruits (12.04), yield (139.51 g) and earlier harvest of the fruits (63.40 days) were observed in variety Winter Dawn under both growing systems. Biochemical characters viz., highest TSS (11.54 0 B), lowest acidity (0.65 %), TSS/acidity ratio (11.3) and total sugars (6.70 %) and overall sensory score were highest in the variety Sweet Charlie followed by Winter Dawn. However, the variety Winter Dawn had better appearance and flavour. It can be concluded that among five varieties evaluated under two growing systems viz., open condition and polyhouse, Winter Dawn and Sweet Charlie are found to be better in yield and quality. Therefore, these varieties can be recommended for commercial cultivation in agroclimatic conditions of Wayanad, Kerala.